2020
DOI: 10.1111/cod.13669
|View full text |Cite
|
Sign up to set email alerts
|

Application of the adverse outcome pathway framework for investigating skin sensitization potential of nanomaterials using new approach methods

Abstract: Background Currently, considerable efforts to standardize methods for accurate assessment of properties and safety aspects of nanomaterials are being made. However, immunomodulation effects upon skin exposure to nanomaterial have not been explored. Objectives To investigate the immunotoxicity of single‐wall carbon nanotubes, titanium dioxide, and fullerene using the current mechanistic understanding of skin sensitization by applying the concept of adverse outcome pathway (AOP). Methods Investigation of the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In summary, the skin sensitization results for GNPs using the two alternative tests were negative. In our study, it was shown that the well-known sensitizer-induced inflammation indicator IL-1alpha was not induced [ 30 , 31 ]. Moreover, when judged considering all the results such as IL-1beta, IL-8 and TNF-alpha, which are cytokines related to acute inflammatory reactions, graphene does not appear to have an inflammatory effect on keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the skin sensitization results for GNPs using the two alternative tests were negative. In our study, it was shown that the well-known sensitizer-induced inflammation indicator IL-1alpha was not induced [ 30 , 31 ]. Moreover, when judged considering all the results such as IL-1beta, IL-8 and TNF-alpha, which are cytokines related to acute inflammatory reactions, graphene does not appear to have an inflammatory effect on keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note that this method has been submitted to OECD and the drafted proposal has been publicized on the OCED website ( OECD, 2016b ; OECD, 2018c ). This method recently has been used to evaluate the role of nanomaterials in skin sensitization ( Bezerra et al, 2021 ).…”
Section: Skin Sensitization Assaymentioning
confidence: 99%
“…To comply with the 3Rs policy, non-animal methods have been proposed to assess potential chemical sensitizers 54,55 . In 2016, the Brazilian National Council for the The recent report by Bezerra et al 60 exemplifies a practical contribution toward the applicability of the existing OECD guidance 59 for skin AOPs and the IATA. These authors evaluated the immunotoxicity of carbon nanotubes containing titanium dioxide and of fullerene.…”
Section: Case Examplesmentioning
confidence: 99%
“…These authors evaluated the immunotoxicity of carbon nanotubes containing titanium dioxide and of fullerene. By using in vitro assays for accurate assessment of skin sensitization, these authors indicated that the nanomaterials were internalized into keratinocytes (KE1), interacted with skin protein-like molecules (KE2), and stimulated inflammatory cytokine production by monocytic cells (KE3) 60 . Accordingly, the nanomaterials were deemed to be skin sensitizers in vitro, indicating that they should be considered for further higher tier studies to support risk assessment, including exposure and dose-response evaluations.…”
Section: Case Examplesmentioning
confidence: 99%